Localization of peripheral pulmonary nodules for thoracoscopic excision: value of CT-guided wire placement - Shah, RM; Spirn, PW; Salazar, AM; Steiner, RM; Cohn, HE; Solit, RW; Wechsler, RJ; Erdman, S (American journal of roentgenology (1976), 1993)
One of the indications for the rapidly expanding use of thoracoscopic surgery as an alternative to thoracotomy is the excision of peripheral lung nodules. Nodules judged too small or too far from the pleural surface to be seen or palpated during thoracoscopy must be localized beforehand. The purpose of this study was to evaluate the feasibility and effectiveness of percutaneous placement of spring hookwires to localize such nodules before video-assisted thoracoscopy. Under CT guidance, 17 nodules in 14 patients were preoperatively localized with the Kopans breast lesion localization system. Three patients who had solitary nodules had thoracoscopic resections for diagnosis because a previous transthoracic needle or transbronchial biopsy had been unsuccessful. Four patients who had lesions less than 8 mm in diameter had thoracoscopic biopsies because transthoracic fine-needle aspiration biopsy was not likely to be diagnostic. Seven patients, who had a total of 10 nodules, had therapeutic wedge resections of either limited metastases or a second bronchogenic carcinoma. Mean nodule diameter was 10 mm (range, 3-20 mm). The mean distance from nodule to costal pleura was 9 mm (range, 0-25 mm). At the end of the procedure, wire placement was confirmed by CT scanning. After thoracoscopy, the surgeons were questioned about the stability and utility of each hookwire localization. In all 17 procedures, a hookwire was placed successfully. In one case, the wire dislodged before thoracoscopy (after a 6-hr preoperative delay and severe bending of the wire during induction of anesthesia). In 16 of the 17 resections, the surgeon thought that thoracoscopic identification of the lesion would not have been possible without hookwire localization. Only one localization, across a major fissure, required placement of a second wire to localize a nodule. Wire-related complications included two instances of serious pain, five cases of clinically insignificant pneumothorax, and one large pneumothorax requiring drainage before a second nodule in the same lung was localized. CT scanning showed presumed local pulmonary hemorrhage in six cases without hemoptysis or hemothorax. CT-guided hookwire localization is easily and safely performed and permits thoracoscopic resection of lung nodules, which might otherwise be impossible.